Treatability and fate of various phosphorus fractions in different wastewater treatment processes - Gu, A Z (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
The increasingly more stringent phosphorus (P) discharge limits, which are below the concentrations reliably achievable with currently available technologies, demand for better understanding of phosphorus removal mechanisms. This study investigated the compositional fractions of phosphorus (P) in various effluents as well as the efficacy of different levels of treatment processes for removing different fractions of P in wastewater. The results showed that BNR can effectively remove most fractions of P, with relatively higher efficiencies (>93%) towards bioavailable forms of P including soluble reactive P (sRP), particulate reactive P (pRP) portion and particulate acid hydrolysable P (pAHP) and, it showed relatively lower efficiency (78%) towards organic P. Soluble acid hydrolysable P (sAHP) was not effectively removed (<40%). Chemical P removal process was more effective for elimination of sRP, sAHP and particulate organic P (pOP), but was not as effective for removing pAHP and, it exhibited nearly no removal of dissolved organic P (DOP). We found that chemical P removal process led to a significant increase in the concentration of pRP by up to 255%, indicating that these pRP (presumably as chemically bounded P) are likely formed through chemical precipitation/co-adsorption. Only 22% and 64% of the pRP was removed through tertiary clarifier and filtration, respectively. This implies that chemical addition converts sRP into particulate-associated P, mostly as pRP that was not easily removed by sedimentation and filtration, therefore, the efficacy of chemical P removal highly depends on the effectiveness of solid and liquid separation process. As more sRP and particulate P were removed through the series of treatment processes, the percentage contribution from organic P increases with the level of treatment due to its recalcitrant nature. Our results indicated that in order to achieve extremely low effluent P levels, technologies and processes that can enhance pRP and DOP removal will be required